ANALISIS STRATEGI PEMASARAN DESA WISATA BRAYUT PANDOWOHARJO KABUPATEN SLEMAN - , ZAHROUL BATUL ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Over time, the respect of the world tourism attraction of Tourism ( ODTW ) growing and varies kinds of activities . The development is one of them namely the existence of alternative activities in the tourism village that existed in the present . The activities offered by considering the state of the city hustle and bustle of the crowded , congested , polluted . This tourism is based ecotourism are returned to the wild . One example is Brayut Pandowoharjo Village, Sleman , Yogyakarta . Looking at the increasing prospect visits annually in the Tourism Village Brayut , certainly not apart from the marketing and promotional activities that have been carried out by the manager . Because, basically, a product can be recognized by consumers melalai marketing activities . Based on the explanation above, the authors are interested in researching about how the marketing strategy that has been done by the manager of Village Tourism Brayut to continue to increase the number of travelers there . Object of research by the author is Village Tourism Brayut , Pandowoharjo , Sleman , Yogyakarta , who pioneered since 1999 and is the oldest village in Sleman Tourism . Data collection techniques that authors use the method of interview , observation and study the literature . Of interview , observation and study the literature , the writers describe the implementation of ecotourism in Brayut Tourism Village , and the authors found that development constraints occur there in . Results of the study authors , efforts to bring tourists to experience success in terms of the number of visits has increased every year dating . Tourists who come to the Tourism Village Brayut are tourists from various regions , including Java , outside Java , and abroad . From 2007 to May 2013 as many as 11 912 tourists as 50 % are students ( ages 6-17 years ) , students from various faculties 9 % , and the public as much as 41 % . Of travelers and 11 912 , 2 % are foreign tourists and 98 % were domestic tourists with total as many as 275 as many as 11,637 domestic tourists and travelers . This shows the level of traffic is still dominated by domestic tourists. The next obstacle in its marketing of the Tourism Village Brayut not possess special marketing division , the authors describe the development direction of future marketing activities managers can search for specific marketing division as well as new innovations in marketing activities primarily through the medium of internet .